1984
DOI: 10.1161/01.cir.69.5.1000
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two different diltiazem treatments on infarct size in ischemic, reperfused porcine hearts.

Abstract: IT IS well accepted that the speed at which ischemic myocytes die depends on the extent of the imbalance between oxygen supply and demand. 2Accordingly, a number of agents have been found that delay the development of infarcts by reducing myocardial oxygen consumption during ischemia.3 Among them are calcium antagonists, a heterogeneous group of compounds that can improve the myocardial oxygen supply-demand balance by depressing myocardial contractility, decreasing heart rate, and inducing coronary vasodilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Coronary artery circulation in pigs presents regional distribution similar to hu mans and a negligible native collateral net work, in contrast with other laboratory ani mals [5][6][7]9], Therefore, the pig is an inter esting model for the study of myocardial effects after transient coronary occlusion (CO) [4,12,14] in many clinical circumstanccs in which coronary collateral network is poorly developed.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery circulation in pigs presents regional distribution similar to hu mans and a negligible native collateral net work, in contrast with other laboratory ani mals [5][6][7]9], Therefore, the pig is an inter esting model for the study of myocardial effects after transient coronary occlusion (CO) [4,12,14] in many clinical circumstanccs in which coronary collateral network is poorly developed.…”
Section: Introductionmentioning
confidence: 99%
“…anipamil, verapamil, calcium antagonist, ischemia, reperfusion, cardioprotection Roberto Ferrari, Riccardo Raddino, Claudio Ceconi, Salvatore Curello, Salvatore Ghielmi, Odoardo Visioli Cattedra di Cardiologia e Cattedra di Chimica, Universita degli Studi di Brescia, Brescia, Italy utilization and decreasing ATP production [2]. These considerations have stimulated, during the last few years, a growing interest in the possibility of reducing ischemic injury with agents commonly referred to as calcium antagonists [3][4][5]. …”
mentioning
confidence: 99%
“…Klein et al [9] observed a similar cardio protective effect on the metabolic situation of the ischemic myocardium in pigs after administration of diltiazem (Ca2+ antago nist). Besides improvement of metabolic pa rameters (increased concentration of ADP and NAD in the myocardium) the authors described diminution of the infarct size of the heart.…”
Section: Discussionmentioning
confidence: 77%